Non-invasive cerebral oxygenation reflects mixed venous oxygen saturation during the varying haemodynamic conditions in patients undergoing transapical transcatheter aortic valve implantation - Paarmann, Hauke (Oxford University Press, 2012)
Transapical transcatheter aortic valve implantation (TA-TAVI) is increasingly used to treat aortic valve stenosis in high-risk patients. Mixed venous oxygen saturation (SvO(2)) is still the ‘gold standard’ for the determination of the systemic oxygen delivery to consumption ratio in cardiac surgery patients. Recent data suggest that regional cerebral oxygen saturation (rScO(2)) determined by near-infrared spectroscopy is closely related to SvO(2). The present study compares rScO(2) and SvO(2) in patients undergoing TA-TAVI. n = 20 cardiac surgery patients scheduled for TA-TAVI were enrolled in this prospective observational study. SvO(2) and rScO(2) were determined at predefined time points during the procedure. Correlation and Bland–Altman analysis of the complete data set showed a correlation coefficient of r(2 )= 0.7 between rScO(2) and SvO(2) (P < 0.0001), a mean difference (bias) of 5.8 with limits of agreement (1.96 SD) of −6.8 to 18.3% and a percentage error of 17.5%. At all predefined time points correlation was moderate (r(2 )= 0.50) to close (r = 0.84), and the percentage error was <24%. RScO(2) determined by near-infrared spectroscopy is correlated to SvO(2) during varying haemodynamic conditions in patients undergoing TA-TAVI. This suggests that rScO(2) is reflective not only of the cerebral, but also of the systemic oxygen balance.